FRI0014 Generation and characterization of monoclonal antibodies from single RA synovial B cells. (23rd January 2014) - Malmström, V.; Amara, K.; Meffre, E.; Klareskog, L.; Wardemann, H.; Steen, J.; Murray, F.
Abstract : Background: Anti-citrulline protein antibodies (ACPA) are a hallmark of HLA-associated RA, but it is still not established whether these antibodies represent a cause or a consequence of arthritis. It is however clear that such antibodies can enhance murine arthritis, but a corresponding effect in patients is difficult to prove. Objectives: We have approached this question by assessing the specificity and immunoglobulin gene characteristics of B cells derived from RA synovial fluid of RA. Methods: We have utilized a method that allows in vitro production of monoclonal antibodies derived from single human memory B cells. To this end we have cloned single flow cytometry purified CD19+IgG+ B cells from synovial fluid of four ACPA+ and three ACPA- RA patients and analyzed the seqences for mutational patterns. Moreover, we have expressed recombinant monoclonal antibodies from three of the ACPA+ and one ACPA- RA patient and tested, by ELISA, the generated antibodies for reactivity to different known citrullinated antigens. Results: On the molecular level, striking differences were found between ACPA+ and ACPA- patients taking into consideration the mutational pattern of the Ig genes. Indeed, based on DNA sequences, we could demonstrate that B cells from ACPA+ patients did not have more total mutations than ACPA- patients but when focusing on the CDR1, 2 and 3 regions of the Ig variable region, the ACPA+ clones clones displayed strikingly more replacement mutations than did the ACPA- clones. Regarding the specificity of the generated monoclonal antibodies, our results so far show citrulline reactive antibodies could be found from the ACPA+ but not from the ACPA- RA patient. These recombinant antibodies demonstrated reactivity, to variable degrees, to CCP and different citrullinated antigens including citrullinated a-enolase, fibrinogen, and vimentin. Conclusions: In summary, our data suggest that citrulline-reactive B cells are common in synovial fluid and the Ig molecules bear clear signs of antigen-driven maturation. Disclosure of Interest: None Declared